Direct and Indirect Roles of Macrophages in Hypertrophic Scar Formation - Feng, Yi; Sun, Zi-Li; Liu, Si-Yu; Wu, Jun-Jie; Zhao, Bin-Hong; Lv, Guo-Zhong; Du, Yong; Yu, Shun; Yang, Ming-Lie; Yuan, Feng-Lai; Zhou, Xiao-Jin (Frontiers in Physiology, 2019)
Abstract Hypertrophic scars are pathological scars that result from abnormal responses to trauma, and could cause serious functional and cosmetic disability. To date, no optimal treatment method has been established. A variety of cell types are involved in hypertrophic scar formation after wound healing, but the underlying molecular mechanisms and cellular origins of hypertrophic scars are not fully understood. Macrophages are major effector cells in the immune response after tissue injury that orchestrates the process of wound healing. Depending on the local microenvironment, macrophages undergo marked phenotypic and functional changes at different stages during scar pathogenesis. This review intends to summarize the direct and indirect roles of macrophages during hypertrophic scar formation. The in vivo depletion of macrophages or blocking their signaling reduces scar formation in experimental models, thereby establishing macrophages as positive regulatory cells in the skin scar formation. In the future, a significant amount of attention should be given to molecular and cellular mechanisms that cause the phenotypic switch of wound macrophages, which may provide novel therapeutic targets for hypertrophic scars.